Intravenous delivery of the toll-like receptor 7 agonist SC1 confers tumor control by inducing a CD8+ T cell response. (3rd July 2019) - Vascotto, Fulvia; Petschenka, Jutta; Walzer, Kerstin C.; Vormehr, Mathias; Brkic, Magdalena; Strobl, Stefan; Rösemann, Roman; Diken, Mustafa; Kreiter, Sebastian; Türeci, Özlem; Sahin, Ugur
ABSTRACT: TLR7 agonists are considered promising drugs for cancer therapy. The currently available compounds are not well tolerated when administered intravenously and therefore are restricted to disease settings amenable for topical application. Here we present the preclinical characterization of SC1, a novel synthetic agonist with exquisite specificity for TLR7. We found that intravenously administered SC1 mediates systemic release of type I interferon, but not of proinflammatory cytokines such as TNFα and IL6, and results in activation of circulating immune cells. Tumors of SC1-treated mice have brisk immune cell infiltrates and are polarized towards a Th1 type signature. Intratumoral CD8 + T cells and CD11b + conventional dendritic cells (cDCs) are significantly increased, plasmacytoid dendritic cells (pDCs) are strongly activated and macrophages are M1 phenotype polarized, whereas myeloid-derived suppressor cells (MDSCs) are decreased. We further show that treatment of mice with SC1 profoundly inhibits the growth of established syngeneic tumors and results in significantly prolonged survival. Mice, which are tumor-free after SC1 treatment are protected from subsequent tumor rechallenge. The antitumor effect of SC1 depends on antigen-specific CD8 + T cells, which we found to be strongly enriched in the tumors of SC1-treated mice. In conclusion, this study shows that systemically administered SC1 mobilizes innate and adaptive immunity and is highly potent as single agent in mice and thereby provides a rationale for clinical testing of this compound.